Cold Agglutinin Disease: A Distinct Clonal B-Cell Lymphoproliferative Disorder of the Bone Marrow - Fina Climent; Joan Cid; Anna Sureda (Hemato, 2022)
Cold agglutinin disease (CAD) is a distinct clinicopathologic entity characterized by clonal B-cell lymphoproliferative disorder in the bone marrow. B-cell gene mutations affect NF-ΚB as well as chromatin modification and remodeling pathways. Clonal immunoglobulins produced by B cells bind to red cells (RBCs) at cold temperatures causing RBC aggregation, complement cascade activation and cold-autoantibody autoimmune hemolytic anemia (cAIHA). The clinical picture shows cold-induced symptoms and cAIHA. Therapeutic options include “wait and watch”, rituximab-based regimens, and complement-directed therapies. Steroids must not be used for treating CAD. New targeted therapies are possibly identified after recent molecular studies.